Future ready : the four pathways to capturing digital value - Woerner, Stephanie L.; Weill, Peter; Sebastian, Ina M. (Ascent Audio, 2023)
It seems like almost every company you can think of has embarked on a "digital transformation" journey. The problem is, many companies start down the road without a good sense of where they are going or a clear idea of how they will create and capture digital value. Not surprisingly, this leads to problems: failure to realize the value from digital in their bottom lines, wasted resources and effort, added complexity and dysfunction. This compact, no-nonsense book provides a solution. In their years of working with senior executives around the world, MIT research scientists Stephanie Woerner, Peter Weill, and Ina Sebastian noticed that these leaders knew they had to transform their businesses, but lacked a coherent framework and a common language-a playbook-to guide and motivate their employees and keep everyone focused on a common goal. Future Ready is that playbook. Based on years of rigorous research with data from more than a thousand companies, the book provides a powerful framework that offers insights into the important dimensions at which a firm must excel in order to be competitive, as well as the organizational disruptions that every firm must manage as part of the transformation journey. The book includes instructive examples, sharp analyses, assessments to help companies benchmark themselves against top performers.